Global citizenship for adult education advancing critical literacies for equity and social justice - Robinson, Petra A.; Williams, Kamala V.; Stojanovic, Maja (Adult educator) (London : Routledge, 2021)
This book promotes the development of nontraditional literacies in adult education, especially as these critical literacies relate to global citizenship, equity, and social justice. As this edited collection argues, a rapidly changing global environment and proliferation of new media technologies have greatly expanded the kinds of literacies that one requires in order to be an engaged global citizen. It is imperative for adult educators and learners to understand systems, organizations, and relationships that influence our lives as citizens of the world. By compiling a comprehensive list of foundational, sociocultural, technological and informational, psychosocial and environmental, and social justice literacies, this volume offers readers theoretical foundations, practical strategies, and additional resources.
Keywords: Adult education; World citizenship; Educational equalization; Social justice and education; EDUCATION / General